Experiences of depression in Yogyakarta, Indonesia - Widiana, Herlina Siwi (Mental health, religion & culture, 2018)
People from different cultural settings may differ in their presentation with depression. Exploration of experiences was assessed through interviews with 20 Javanese adults aged from 18 to 55 years in Yogyakarta, Indonesia, who had mild to moderate depression. Five themes emerged from the interviews as characteristic of Javanese experiences of depression: internalised and externalised emotions, loss of interest in social and religious activities, disturbance in cognition, the presence of physical symptoms, and suicidal ideation. Javanese respondents used particular terms to explain their depression. Attending to how people’s expression and experiences of their depression might enhance the capacity of clinicians to understand cultural variation, in order to respond appropriately to their clients.